Here, there, and everywhere: How pathogenic Escherichia coli sense and respond to gastrointestinal biogeography. (31st October 2019) - Woodward, Sarah E.; Krekhno, Zakhar; Finlay, B. Brett
Abstract: Gastrointestinal (GI) pathogens enteropathogenic and enterohaemorrhagic Escherichia coli (EPEC and EHEC), and related mouse pathogen Citrobacter rodentium, are referred to as attaching and effacing (AE) pathogens for the lesions they form upon colonisation of the host epithelium. EPEC, EHEC, and C. rodentium are well known to use a type III secretion system to intimately attach to intestinal cells and secrete bacterial effectors to manipulate host cell processes. Less well known is the ability of AE pathogens to overcome significant physiological and microbial barriers and target specific gut niches for initial colonisation of the host epithelium. This review considers recent work highlighting the biogeography of the GI tract as it applies to colonisation by enteric pathogens, including environmental barriers to enteric infection, signals sensed by AE pathogens for navigation of the GI tract, and the tools AE pathogens use to respond to the changing host environment.